Engineering tribology - Stachowiak, G. W. (Butterworth-Heinemann, 2014)
An introductory reference focusing on the key concepts and engineering implications of tribology, the book brings together the relevant knowledge from different fields needed to achieve effective analysis and control of friction and wear. Updated to cover recent advances in tribology, this new edition includes new sections on ionic and mesogenic lubricants, surface texturing, and multiscale characterization of 3D surfaces and coatings. Current trends in nanotribology are discussed, such as those relating to lubricants, coatings and composites, and geotribology is introduced. This book offers a comprehensive overview of the mechanisms of wear, lubrication and friction in an accessible manner designed to aid novice engineers, non-specialists and students; Provides a reader-friendly approach to the subject using illustrations to break down the typically complex problems associated with tribology; and ncludes end-of-chapter problems to test understanding, with solutions provided.